Dopaminergic Modulation of Glomerular Circuits in the Mouse Olfactory Bulb - Liu, Shaolin (Frontiers in Cellular Neuroscience, 2020)
Dopaminergic neurons are located in several brain areas including the olfactory bulb (OB) and involved in many physiological and pathophysiological processes. In the OB, dopamine (DA) is released exclusively by a population of interneurons termed short axon cells (SACs) in the glomerular layer, the initial synaptic integration site of the whole olfactory system. SACs corelease GABA and extend their processes to many glomeruli forming the interglomerular circuit. Two major groups of DA receptors D1-like (D1LRs) and D2-like (D2LRs) types are differentially distributed in the OB, i.e., D1LRs are broadly present except the most superficial olfactory nerve (ON) layer while D2LRs are predominantly confined to the ON and glomerular layers, suggesting that they mediate different physiological functions. In contrast to the well-known D2LR-mediated presynaptic inhibition of ON terminals in the OB, the cellular and circuit targets of the D1LR-mediated DA actions remain unclear even though D1LR activation improves odor detection and discrimination. We recently demonstrated that endogenous DA released from SACs or exogenous DA excites a population of excitatory glomerular neurons termed external tufted cells (ETCs) via D1LRs. But the physiological significance of this D1LR activation is largely unknown. In the present study we addressed these questions by a systematic examination of exogenous DA actions on synaptic activities and excitabilities in most glomerular neurons and OB output neurons with the following major findings: (1) DA via D1LRs enhances OB output by potentiating the ETC-mediated feedforward excitation to the OB output neurons but suppresses spontaneous excitatory synaptic activities in both types of inhibitory glomerular interneurons periglomerular (PGCs) and SACs; (2) this suppression of excitatory synaptic activities in PGCs and SACs depends on activation of GABAB receptors; (3) DA via D1LRs augments spontaneous inhibitory synaptic activities in all glomerular neurons and OB output neurons; (4) DA selectively activates SACs via D1LRs. These findings suggest that actitation of D1LRs elevates the system’s sensitivity to odor stimuli and provide a mechanistic basis for the functional roles of DA in modulating odor detection and discrimination.